2018
DOI: 10.1371/journal.pone.0198187
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk for neurodegenerative disorders, and its overlap with cognitive ability and physical function

Abstract: Neurodegenerative disorders are associated with impaired cognitive function and worse physical health outcomes. This study aims to test whether polygenic risk for Alzheimer’s disease, Amyotrophic Lateral Sclerosis (ALS), or frontotemporal dementia (FTD) is associated with cognitive function and physical health in the UK Biobank, a cohort of healthy individuals. Group-based analyses were then performed to compare the top and bottom 10% for the three neurodegenerative polygenic risk scores; these groups were com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Dementia is a clinical state caused by neurodegeneration and is characterized by a loss of function in cognitive domains and undesirable changes in behavior. Several types of neurodegenerative diseases were described [1,2,3,4], including Alzheimer’s disease (AD), Parkinson’s disease (PD), frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS), prion diseases, and Huntington’s disease, which may share clinical and pathologic features [5]. The common feature of the neurodegenerative diseases could be the abnormal protein aggregates in the central nervous system [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dementia is a clinical state caused by neurodegeneration and is characterized by a loss of function in cognitive domains and undesirable changes in behavior. Several types of neurodegenerative diseases were described [1,2,3,4], including Alzheimer’s disease (AD), Parkinson’s disease (PD), frontotemporal dementia (FTD), amyotrophic lateral sclerosis (ALS), prion diseases, and Huntington’s disease, which may share clinical and pathologic features [5]. The common feature of the neurodegenerative diseases could be the abnormal protein aggregates in the central nervous system [6].…”
Section: Introductionmentioning
confidence: 99%
“…While cognitive dysfunction has been more frequently linked to genetic mutations causally associated with ALS, such as C9ORF72 repeat expansions [43], studies examining individual SNPs have demonstrated quantitative-trait modification of cognitive performance and cortical disease burden [24,25]. However, mounting evidence suggests that there are polygenic, rather than single allele, modifiers of disease risk and phenotype in ALS and related neurodegenerative diseases [22,23,26]. Our observation of polygenic association between of 27 SNPs and the ECAS ALS-Specific score, a combined measure of executive, language, and verbal fluency domains most commonly affected in ALS, is consistent with the idea of polygenic contribution to phenotypic variability in ALS.…”
Section: Discussionmentioning
confidence: 99%
“…22,24 However, mounting evidence suggests that there are polygenic, rather than single allele, modifiers of disease risk and phenotype in ALS and related neurodegenerative diseases. 16,17,24 Our observation of 26 genetic variants collectively associating with the ECAS ALS-Specific score -a combined measure of executive, language, and verbal fluency domains most commonly affected in ALS -is consistent with the idea of polygenic contribution to phenotypic variability in ALS. Notably, our observed polygenic association in the CReATe PGB Cohort appears specific to cognitive variability in ALS: we demonstrate relative independence of cognitive performance and motor disease severity (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurodegenerative diseases are a series of diseases with insidious onset and slow progression, characterized by aggregation of abnormal proteins in neurons and other cells, including AD, Parkinson’s disease (PD), amyotrophic lateral sclerosis (ALS), DLB, and FTD etc. Neurodegenerative diseases have some neuropathology, clinical and/or genetic crossover 13,14 . For example, Parkinson’s disease dementia (PDD) has both α‐synuclein and Aβ deposits in the brain that may co‐cause the disease onset 15,16 .…”
Section: Introductionmentioning
confidence: 99%